On the morality of vaccination tourism - Espíndola Mata, Juan (Bioethics, 2022)
Vaccination tourism (whereby citizens of one nation travel to a different, usually more developed nation to receive a vaccine unavailable or with little availability at home) during the COVID pandemic raises a host of moral issues and is usually met with criticism. From the perspective of the society of origin, the criticism is that those who use their socio-economic privileges to go abroad and receive the vaccine ahead of other citizens instead of ‘making the line’ act objectionably because in doing so they use their purchasing power to obtain a benefit that should not be distributed like any other product in the market. From the perspective of the society of destination, the criticism is that citizens and residents should receive the vaccines first; after all, their government purchased vaccines (with their taxes) to immunize the local population. The paper calls into question both objections to vaccination tourism. There might be other reasons to oppose it, but this pair of objections cannot ground a moral criticism of the practice.